Antifreeze activity enhancement by site directed mutagenesis on an antifreeze protein from the beetle Rhagium mordax. Issue 9 (26th March 2014) - Friis, Dennis Steven; Kristiansen, Erlend; von Solms, Nicolas; Ramløv, Hans
Abstract : The ice binding motifs of insect antifreeze proteins (AFPs) mainly consist of repetitive TxT motifs aligned on a flat face of the protein. However, these motifs often contain non‐threonines that disrupt the TxT pattern. We substituted two such disruptive amino acids located in the ice binding face of an AFP from Rhagium mordax with threonine. Furthermore, a mutant with an extra ice facing TxT motif was constructed. These mutants showed enhanced antifreeze activity compared to the wild type at low concentrations. However, extrapolating the data indicates that the wild type will become the most active at concentrations above 270 μmol. Abstract : Antifreeze proteins contain obstructing amino acids in their ice binding sites. These were removed in an insect antifreeze protein by site directed mutagenesis. Antifreeze activity was substantially increased at low and medium concentrations. A change in the relation between antifreeze activity and concentration was observed.